Patterns of psychiatry morbidity in referred patients attending psychiatry out patient department in a tertiary centre - Malla, Deep Prakash; Basnet, Rachana Sharma; Pokharel, Aakriti Malla (Journal of Kathmandu Medical College, 2017)
Background: Consultation-liaison psychiatry is an important part of psychiatry dealing with cases having co morbid general medical conditions. Psychiatrists need to be involved in evaluation of patients referred from other specialties. Objectives: To assess the patterns of psychiatry morbidity in referred patients attending psychiatry out patient department of Kathmandu Medical College. Methods: A total of 200 patients were referred to the department of psychiatry from different out patient departments during a period of six months. Each of them underwent a detailed psychiatric evaluation. Results: The mean age of the patients evaluated was 36.03 years; most of them were females (66.5%), married (67%), educated up to class seven (28%) and housewives (32.5%) living in a nuclear family (62.5%) coming from a middle income socio-economic status (75%). More than half (52%) referrals were from Medical ward coming with the chief complaint of headache (18.5%) followed by disturbance in sleep pattern (17%) and pain in more than three sites (17%). The most common psychiatric diagnosis was depression (49%) followed by anxiety (35.5%). A majority of the patients (55%) perceived their illness to be neurological and had received alternative treatment from a faith healer (26%) before being referred to the psychiatric out patient department. Conclusion: Psychiatric consultation was sought mostly by medical out patient department that had maximum number of patients. The commonest diagnosis seen in the referred out-patients was depression and anxiety disorder. Patients mostly presented with vague somatic complaints such as headache, disturbance in sleep pattern and pain over more than three sites of the body.